Kebijakan PNG Solutions dalam Menangani Pengungsi dan Pencari Suaka di Australia Periode Kevin Rudd - Rolas Sauriana Tamba; Ika Riswanti Putranti; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2018)
Australia is a country that has ratified the 1951 Refugee Convention. However, during the regime of Prime Minister Kevin Rudd in 2013, Kevin Rudd released a tough policy against refugees and asylum seekers who came to Australia called the PNG Solution policy. PNG Solution is a policy provide that every refugee and asylum seeker arriving without a passport or visa, using a ship, will not resettle in Australia. They will be resettled in Papua New Guinea. This research will explain, the reasons of Australia, create the PNG Solutions policy, against refugees and asylum seekers in Australia. Qualitative research method, with explanative type, used in this research to discuss the policy of PNG Solution and the factors drive in determining the policy. Meanwhile, the concept used to explain in this research is concept of Foreign Policy Analysis, that is Internal and External Setting from Richard Synder, Bruck and Sapin. Data were collected using official government literature and archive studies. The results show that, internal factors are Labors Party, the situational characteristics of Australia, and public opinion is more dominant in Australian foreign policy. Meanwhile, the external factors, have no influence in decision making.